Experimental and Theoretical Deflections of Hybrid Composite Sandwich Panel under Four-point Bending Load - Jauhar Fajrin; Yan Zhuge; Hao Wang; Frank Bullen (Civil Engineering Dimension, 2017)
This paper presents a comparison of theoretical and experimental deflection of a hybrid sandwich panel under four-point bending load. The paper initially presents few basic equations developed under three-point load, followed by development of model under four-point bending load and a comparative analysis between theoretical and experimental results. It was found that the proposed model for predicting the deflection of hybrid sandwich panels provided fair agreement with the experimental values. Most of the sandwich panels showed theoretical deflection values higher than the experimental values, which is desirable in the design. It was also noticed that the introduction of intermediate layer does not contribute much to reduce the deflection of sandwich panel as the main contributor for the total deflection was the shear deformation of the core that mostly determined by the geometric of the samples and the thickness of the core.